Catching fire - Collins, Suzanne; Parisi, Elizabeth B.; Scholastic Press (New York Scholastic Press e(Printed in Malaysia), 2009)
By winning the annual Hunger Games, District 12 tributes Katniss Everdeen and Peeta Mellark have secured a life of safety and plenty for themselves and their families, but because they won by defying the rules, they unwittingly become the faces of an impending rebellion.
Part 1 The spark -- Part 2 The quell -- Part 3 The enemy.
"Book design by Elizabeth B. Parisi"--t.p. verso.
Accelerated Reader/Renaissance Learning
Keywords: Insurgency -- Juvenile fiction; Survival -- Juvenile fiction; Television programs -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Contests -- Juvenile fiction; Dystopias -- Juvenile fiction; Girls -- Juvenile fiction; Courage -- Juvenile fiction; Adventure and adventurers; Television programs -- Fiction; Contests -- Fiction; Insurgency -- Fiction; Young adult fiction; Science fiction -- Juvenile; Science fiction; Dust jackets (Bindings) -- 2009.